ЛЮМИНИСЦЕНТТІ БАКТЕРИЯЛАРДЫҢ ТЕСТ-ЖҮЙЕЛЕРІН ПАЙДАЛАНЫП БІР ҚАБАТТЫ КӨМІРТЕКТІ НАНОТҮТІКШЕЛЕРДІҢ БИОЛОГИЯЛЫҚ ЭФФЕКТТЕРІН БИОТЕСТІЛЕУ (Experimental biology, 2017)
The effect of a single-wall carbon nanotubes (carbon SWNT) on bacterial cells Escherichia coli K12 TG1 with cloned luxoperon of natural marine bacteria Photobacterium leiognathi was studied. Using atom force microscopy (AFM) bacterial cell morphological changes were revealed and cell viability decrease controlled by the number of colony-forming units was registered. It was shown that prior to these changes we can observe changes in the intensity of oxygen consumption and bacterial luminescenceintensity. This allows to recommend well-known and easy-to-use bioluminescent test for initial testing of nanomaterial toxicity, using for this purpose living bacteria cultures as well as lyophilized biosensors «Ecolum».
Keywords: carbon nanotubes; Escherichia; biosensors